1973
DOI: 10.1111/j.1471-0528.1973.tb11197.x
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Growth and Placental Function in Patients With Placenta Praevia

Abstract: Fetal growth was assessed by serial ultrasound cephalometry in 150 patients with uncomplicated placenta praevia and certain menstrual dates who were treated expectantly. Placental function was assessed by serial 24-hour total maternal urinary oestrogen assays. There were 24 (16 per cent) small-for-dates infants, more accurately predicted by serial cephalometry than by serial maternal urinary oestrogen assays. There was good correlation between fetal growth and the number of episodes of bleeding in pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

1975
1975
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(9 citation statements)
references
References 9 publications
1
8
0
Order By: Relevance
“…Varma (13) showed an increased incidence of fetal growth retardation in her patients with placenta praevia as did Chapman et al( 4) in their patients with a low-lying placenta on early scan. Our study has not shown this, and like Wexler and Gottesfeld (14) we found no other pregnancy abnormalities associated with a low-lying placenta.…”
Section: Diagnosis Of Low-lying Placentamentioning
confidence: 51%
“…Varma (13) showed an increased incidence of fetal growth retardation in her patients with placenta praevia as did Chapman et al( 4) in their patients with a low-lying placenta on early scan. Our study has not shown this, and like Wexler and Gottesfeld (14) we found no other pregnancy abnormalities associated with a low-lying placenta.…”
Section: Diagnosis Of Low-lying Placentamentioning
confidence: 51%
“…Other studies have reported IUGR in cases of placenta previa in the range of 16% to 19%. 15,16 However, in a recent study in which other factors responsible for IUGR (diabetes, hypertension, etc.) were controlled, no significant increase in the incidence of small for gestational age babies was shown in cases of placenta previa.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies assessing the association between placenta previa fetal growth restriction have yielded conflicting results. 8, 9 …”
Section: Introductionmentioning
confidence: 99%